Chronic Stress Triggers Expression of Immediate Early Genes and Differentially Affects the Expression of AMPA and NMDA Subunits in Dorsal and Ventral Hippocampus of Rats - Pacheco, Anibal; Aguayo, Felipe I.; Aliaga, Esteban; Muñoz, Mauricio; García-Rojo, Gonzalo; Olave, Felipe A.; Parra-Fiedler, Nicolas A.; García-Pérez, Alexandra; Tejos-Bravo, Macarena; Rojas, Paulina S.; Parra, Claudio S.; Fiedler, Jenny L. (Frontiers in Molecular Neuroscience, 2017)
Previous studies in rats have demonstrated that chronic restraint stress triggers anhedonia, depressive-like behaviors, anxiety and a reduction in dendritic spine density in hippocampal neurons. In this study, we compared the effect of repeated stress on the expression of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) receptor subunits in dorsal and ventral hippocampus. Adult male Sprague-Dawley rats were randomly divided into control and stressed groups, and were daily restrained in their motion (2.5 h/day) during 14 days. We found that chronic stress promotes an increase in cFOS mRNA levels in both hippocampal areas, although it was observed a reduction in the immunoreactivity at pyramidal cell layer. Furthermore, Arc mRNAs levels were increased in both dorsal and ventral hippocampus, accompanied by an increase in Arc immunoreactivity in dendritic hippocampal layers. Furthermore, stress triggered a reduction in PSD-95 and NR1 protein levels in whole extract of dorsal and ventral hippocampus. Moreover, a reduction in NR2A/NR2B ratio was observed only in dorsal pole. In synaptosomal fractions, we detected a rise in NR1 in dorsal hippocampus. By indirect immunofluorescence we found that NR1 subunits rise, especially in neuropil areas of dorsal, but not ventral hippocampus. In relation to AMPA receptor subunits, chronic stress did not trigger any change, either in dorsal or ventral hippocampal areas. These data suggest that dorsal hippocampus is more sensitive than ventral hippocampus to chronic stress exposure, mainly altering the expression of NMDA receptor subunits, and probably favors changes in the configuration of this receptor that may influence the function of this area.